Pengaruh Pemberian Ekstrak Buah Naga Putih (Hylocereus undatus) terhadap Kerusakan Histologis Sel Ginjal Mencit (Mus musculus) yang Diinduksi Parasetamol - Caesaria Christ Haryadi; Endang Listyaningsih; Bhisma Murti (Nexus Biomedika, 2012)
Background: White dragon fruit (Hylocereus undatus) contains antioxidant substances in the form of vitamin A, C, E, and polyphenol that are reported to be nephroprotective. This study was aimed to verify the effect of white dragon fruit extract and its increasing doses toward paracetamol-induced damage of renal cell of mouse (Mus musculus). Methods: This study was a Randomized Controlled Trial in design. Samples were twenty eight Swiss webster type mice divided into 4 groups randomly, being seven mice in each group. Aquades were administered to mice in control group (KK) and the first group (KP1), while white dragon fruit extract were administered to the second group (KP2) and the third group (KP3) with the dose of 70 mg/20 g BB weight and 140 ml/20 g weight for 14 days, respectively. Paracetamol were administered to KP1, KP2, KP3, with dose 5.07 mg/ 20 g weight on day 12th, 13th and 14th. On day 15th, mice were sacrificed with neck dislocation. Renal cell slides were made and stained by HE. Renal histological is analysed and scored base on quantification of renal histological damage. Data were analyzed by One-Way ANOVA test and Post Hoc test. Results: One-Way ANOVA showed that there was a significant difference between groups. Result of LSD method showed that there were significant of differences between KK-KP1, KK-KP2, KP1-KP2, KP1-KP3 and KP2-KP3 groups, respectively; while no significant different was found between KK-KP3. Conclusion: The administration of white dragon fruit extract might prevent the mice renal cell damage. The increasing doses of white dragon fruit extract induce protection effect towards the renal cell damage of mice induced by paracetamol Key words : white dragon fruit extract, paracetamol, renal cell damage.